Aetiological Factors of Urogenital Fistula and the Treatment Outcome of Patients with Urogenital Fistula Admitted in Rajshahi Medical College Hospital, Rajshahi - Razzaque, Sharmin; Nahar, Nazmun; Jesmin, Sahela; Akhter, Hasina (TAJ: Journal of Teachers Association, 2018)
Urogenital fistulas, majority of which are of vesicovaginal fistulas are commonly caused by prolong obstructed labor and is one of the worst complications of childbirth and poor obstetric care. With the advancement of health care delivery system aetiology of urogenital fistula is also changing in our country. The objective of this study is to create awareness about urogenital fistula, to evaluate the aetiology, profile of the patients and outcome of surgical repair in RMCH. It was a cross-sectional type of observational study having descriptive component of a total 68 cases of urogenital fistula admitted in the department of Obstetrics and Gynaecology, RMCH over a period of one year and six months from January 2009 to July 2010. The incidence among patients admitted in Obstetrics and Gynae was 0.45% and among Gynae patient’s incidence was 1.1%. Majority of the patients were young primipara, short stature and malnourished, coming from lower socio-economic condition of rural areas. Obstructed labour 21(30.8%) was the most common cause of urogenital fistula, followed by gynecological surgeries mainly hysterectomies 19 (27.3%), corrosive application 7 (10%) a rare cause but was found in high rate in this study. A total no of 50 patients underwent surgery. Overall success rate was 46 (92%) and functionally failed with a failure in 4 (8%) cases. The etiology urogenital fistula is preventable and all types of urinary fistula can be repair. Improvement in maternity care in rural areas, easy approach to specialist care and better training of staff in instrumental deliveries may help to decrease the incidence of these fistulas. TAJ 2016; 29(2): 11-15